Learning sources of science concepts and process skills of grade 2 pupils - Alcazar, Antoniette V. (2009)
Thirty randomly selected Grade 2 pupils participated in this study which focused on what concepts and process skills the grade 2 pupils acquired. The data were gathered through a teacher-made test and a semi-structured interview guide. Based on the study, the learning sources that influenced the pupils most in their acquisition of the science conceptions and process skills were the school and the family. The interview results showed that the school has the greatest influence in the acquisition of science concepts and process skills. This influence is carried on to the daily routines both in school and pupils' homes. Through doing and observing things, pupil can strengthen the concepts and skills they learned in school.